2021
DOI: 10.3390/ijms221910570
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Vectors Expressing Eight Multiplex Guide RNAs of CRISPR/Cas9 Efficiently Disrupted Diverse Hepatitis B Virus Gene Derived from Heterogeneous Patient

Abstract: Hepatitis B virus (HBV) chronically infects more than 240 million people worldwide, causing chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC). Genome editing using CRISPR/Cas9 could provide new therapies because it can directly disrupt HBV genomes. However, because HBV genome sequences are highly diverse, the identical target sequence of guide RNA (gRNA), 20 nucleotides in length, is not necessarily present intact in the target HBV DNA in heterogeneous patients. Consequently, possible genome-edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The Ad containing eight multiple gRNA units not only ensures that the target gene is knocked out multiple times, but also solves the problem of off-target effects and escape mutants in genome editing therapy. 208 …”
Section: Application Of Adenoviral Vectors For Gene Editingmentioning
confidence: 99%
“…The Ad containing eight multiple gRNA units not only ensures that the target gene is knocked out multiple times, but also solves the problem of off-target effects and escape mutants in genome editing therapy. 208 …”
Section: Application Of Adenoviral Vectors For Gene Editingmentioning
confidence: 99%
“…Additionally, some new strategies have been utilized to clear HBV with adenovirus vectors. For example, adenovirus was designed to deliver a CRISPR/Cas9 system and a single guide RNA (gRNA) system to degrade the HBV genome [96,97].…”
Section: Therapeutic Vaccines For Hbvmentioning
confidence: 99%
“…These gene editors mediate sequence-specific deleterious mutations within the HBV DNA [ 22 ]. Although AdV-based anti-HBV TALEN delivery is not encouraging [ 59 ], promising outcomes when using AdVs to deliver anti-HBV CRISPR/Cas sequences have been reported [ 60 , 61 ].…”
Section: Adenoviruses As Vectors Of Gene Therapy Against Hbvmentioning
confidence: 99%
“…A recent study by Kato et al successfully demonstrated the efficacy of an AdV expressing a CRISPR/Cas9 system with eight guide RNAs (gRNAs) targeting the HBV X gene ( HBx ) [ 60 ]. In this study, use of an AdV was ideal as the increased carrying capacity of the AdV allowed for inclusion of 8 gRNAs and a large Cas protein-encoding sequence isolated from Streptococcus pyogenes , spCas9.…”
Section: Adenoviruses As Vectors Of Gene Therapy Against Hbvmentioning
confidence: 99%